Performance Evaluation of Class A LoRa Communications - Pacheco, João Artur Marcelino (2019)
Recently, Low Power Wide Area Networks (LPWANs) have attracted a great interest due to the need of connecting more and more devices to the so-called Internet of Things (IoT). This thesis explores LoRa’s suitability and performance within this paradigm, through a theoretical approach as well as through practical data acquired in multiple field campaigns. First, a performance evaluation model of LoRa class A devices is proposed. The model is meant to characterize the performance of LoRa’s Uplink communications where both physical layer (PHY) and medium access control (MAC) are taken into account. By admitting a uniform spatial distribution of the devices, the performance characterization of the PHY-layer is studied through the derivation of the probability of successfully decoding multiple frames that were transmitted with the same spreading factor and at the same time. The MAC performance is evaluated by admitting that the inter-arrival time of the frames generated by each LoRa device is exponentially distributed. A typical LoRaWAN operating scenario is considered, where the transmissions of LoRa Class A devices suffer path-loss, shadowing and Rayleigh fading. Numerical results obtained with the modeling methodology are compared with simulation results, and the validation of the proposed model is discussed for different levels of traffic load and PHY-layer conditions. Due to the possibility of capturing multiple frames simultaneously, the maximum achievable performance of the PHY/MAC LoRa scheme according to the signal-to-interference-plus-noise ratio (SINR) is considered. The contribution of this model is primarily focused on studying the average number of successfully received LoRa frames, which establishes a performance upper bound due to the optimal capture condition considered in the PHY-layer. In the second stage of this work a practical LoRa point-to-point network was deployed to characterize LoRa’s performance in a practical way. Performance was assessed through data collected in the course of several experiments, positioning the transmitter in diverse locations and environments. This work reports statistics of the received packets and different metrics gathered from the physical-layer.